Mathematical Modelling and Control System Development of a Remote Controlled, IMU Stabilised Hexapod Robot - Christopher, Ross (Department of Mechanical Engineering, 2020)
Walking robots are useful in search and rescue applications due to their ability to navigate uneven and complex terrain. A hexapod robot has been developed by the Robotics and Agents Research Lab at UCT, however multiple inadequacies have become evident. This work aims to produce a mathematical model of the hexapod and using this model, implement an effective control algorithm to achieve a smooth walking motion and overcome the original flaws. The mathematical model was integrated with the mechanical structure of the hexapod and controlled by a micro-controller. This micro-controller allows for a rapid start-up and low power consumption when compared to previous iterations of the hexapod. Using a path generation algorithm sets of foot positions and velocities are generated. Generating these points in real time allows for walking in any direction without any pre-defined foot positions. To enable attitude control of the hexapod body, an inertial measurement unit was added to the hexapod. By using a PID controller the IMU pitch and roll data was used to control a height offset of each foot of the hexapod, allowing for stabilisation of the hexapod body. An improved wireless remote control was developed to facilitate communication with a host computer. The remote system has a graphical user interface allowing for walking control and status information feedback, such as error information and current battery voltage. Walking tests have shown that the hexapod walks successfully with a smooth tripod gait using the path generation algorithm. Stabilisation tests have shown that the hexapod is capable of stabilising itself after a disturbance to its pitch and/or roll in ±2.5 seconds with a steady state error of ±0.001 radians. This proves that the hexapod robot can be controlled wirelessly while walking in any direction with a stabilised body. This is beneficial in search and rescue as the hexapod has a high degree of manoeuvrability to access areas too dangerous for rescuers to access. With cameras mounted on the stabilised body, it can be used to locate survivors in a disaster area and assist rescuers in recovering them with speed.